The Relationship of the Level of Knowledge With Community Motivation for Blood Donation in Rt 02 Rw 14 Serengan District, Surakarta City - Syarifah syarifah; Diva Nur Azizah (International Journal of Natural and Health Sciences, 2023)
To determine the relationship between the level of knowledge and the community's motivation to donate blood in RT 02 RW 14 Serengan Village, Surakarta City. This method uses an analytic survey research method with a quantitative approach to the design of a cross sectional design . From the results carried out it shows that the results of the knowledge level of 98.5% are in the good and 1.5% are in the bad. And the motivational result of blood donation is 100% high. The results of the analysis of the two variables using the Spearman Rho test analysis were 0.082 > 0.05, so it can be concluded that there is no significant relationship between the variable level of knowledge and motivation. Conclusion is most of the level of knowledge of blood donors in the good is 98.5%. Most of the motivation of donors in the high category is 100%. In the correlation test using the Spearman Rho test , the significant value was 0.082 > 0.05, so it can be said that there is no significant relationship between knowledge about blood donors and people's motivation to donate blood at RT 02 RW 14 Serengan Village, Surakarta City